Analysis of bile acid profile in plasma to differentiate cholangiocarcinoma from benign biliary diseases and healthy controls. Issue 205 (January 2021) - Zhang, Xiaofen; Yang, Ziyao; Shi, Ziyu; Zhu, Zijia; Li, Cai; Du, Zhicheng; Zhang, Yiding; Wang, Zipeng; Jiao, Zhenrui; Tian, Xin; Zhang, Ji; Zhai, Wenlong; et al.
Graphical abstract: Highlights: Bile acids (BAs) are considered as causative agents for cholangiocarcinoma (CCA). We developed a rapid and sensitive method for determination of BAs using LC–MS/MS. Significantly higher conjugated BAs and lower unconjugated BAs were observed in CCA. A panel of 2 BAs (CDCA and TCDCA) may serve as diagnostic biomarkers for CCA. Abstract: Bile acids (BAs) are currently considered as causative agents for Cholangiocarcinoma (CCA). However, the profile of circulating BAs in CCA have not been well characterized. The aim of this study was to describe the alterations of BAs metabolism in patients with CCA compared to benign biliary diseases (BBD) and healthy controls (HC), and to discover the specific BAs as biomarkers for CCA diagnosis. The concentrations of 15 BAs in plasma were measured in a total of 329 subjects, including patients with BBD, CCA, gallbladder cancer (GC), hepatocellular carcinoma (HCC), and healthy subjects, using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Binary logistic regression analysis was used to build a diagnostic model for CCA. An imbalance in the ratio of conjugated to unconjugated BAs was observed in CCA patients compared to BBD and HC groups, with higher conjugated BAs and lower unconjugated BAs. A panel of 2 BA metabolites consisting of CDCA and TCDCA showed high diagnostic performance for CCA versus BBD and CCA versus HC, with higher AUC, sensitivity and specificity than carbohydrate antigen 19−9 (CA 199), clinically employed CCA biomarker. Importantly, HCC and GC samples were also included to confirm specificity of the BA biomarkers for CCA diagnosis. In summary, specific changes in plasma concentrations of BAs may serve as diagnostic biomarkers for distinguishing CCA from BBD and HC, with higher performance than CA199.